A Case of Down Syndrome Who Developed Pancreatic Cancer: A Case Report and Review of Literature - Purvey, Sneha; Hanna, Mina; Shaib, Walid; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2010)
No abstract available. Image: Trisomy 21 chromosome - Down syndrome (Author: Alexey Ratnikov; Wikimedia Commons)